Characterization of write-once blu-ray disk containing Cu-Al/Si recording layer using transmission electron microscopy - Mai, Hung-Chuan; Hsieh, Tsung-Eong; Jeng, Shiang-Yao (My University, 2011)
Microstructure change in write-once blu-ray disk containing Cu-Al/Si recording layer was investigated by transmission electron microscopy. Nanoscale crystallites were found to comprise of the Cu-Al/Si recording layer before and after signal writing and the energy dispersive spectroscopy revealed insignificant composition fluctuation in disk sample. Analytical results indicated the signal properties of disk samples are correlated with a moderate improvement of crystallinity and the formation of Cu and Si solid-solution phases due to element mixing in mark area, rather than the formation of Cu(3)Si silicide and recrystallization of recording layer as reported by previous studies. (C) 2011 American Institute of Physics. [doi:10.1063/1.3560053]